Malignant ventricular arrhythmias in patients with severe acute respiratory distress syndrome due to COVID-19 without significant structural heart disease (2020)
Since December 2019, the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has resulted in a pandemic of novel coronavirus (COVID-19) infections. Although predominantly a respiratory illness that can cause acute respiratory distress syndrome (ARDS), data suggest cardiovascular involvement contributes significantly to the disease’s mortality. Data from Wuhan, China, demonstrated patients with pre-existing cardiovascular disease and elevated troponin levels had 69.44% mortality